The effect of wind load to non-engineering roof system - Muhammad Hashra Izreen, Mohd Hashidin (2014)
Roof collapse due to wind load impact on roof sheeting during thunderstorm was reported. This failure of roof sheeting was lead to destruction to the nonengineering house. In most cases, failure of roof sheeting based on two points, either on material roof sheeting or at Connection of roof sheeting. It was observed that the most failure of roof sheeting is likely occurred for non-engineering building. Base on MS 1553:2002 wind load for building structure, structure element should be able to resist wind load up to 32.5 m/s. Therefore this study is conducted to identify the possibility of the failure of Corrugated Galvanised Iron roof sheeting for non engineering buildings. The study focus on the connection between roof CGI sheet and purlin. Nail connection are been used in this study, while 4 different spacing distance between connection are used which are 300 mm. 450 mm, 600 mm and 900 mm. Finite Element Software were used in this study to analyse and identify the load distribution. From the result it shown that the maximum spacing of nail connection is 500 mm to resist the wind load recommended by MS 1553:2002. From the result it can be conclude enclose by increasing the spacing of connection it will lead to increase the failure of CGI roof sheeting.